Coping strategies and perceived burden among caregivers of frail elderly with mental disorders attending teaching hospital: A cross-sectional study - Anjana Maharjan; Shobha Laxmi Bajracharya (PLoS ONE, 2026)
Caregivers of frail elderly with mental illness undergo various practical problems, however, adaptive coping skills help to reduce perceived caregiver burden. This study aimed to identify the coping strategies and perceived burden among caregivers of frail elderly with mental disorders. A cross-sectional study was conducted among 129 conveniently selected caregivers of frail elderly with mental disorders at Patan Hospital. Data were collected using a face-to-face interview technique. The Nepali versions of Brief Cope (28 items) and Zarit Burden Interview (ZBI-22 items) were used to assess coping skills and burden respectively. Descriptive and statistical tests (Chi-square, Pearson’s correlation, and Logistic regression) were used to inferential analysis using SPSS version 16. Caregivers most commonly used problem-focused (29.19 ± 3.09; p = 0.112) and emotion-focused (33.16 ± 4.91; p = 0.057) coping strategies. Nearly half of the caregivers (48.1%) reported little/no burden, while 15.5% reported severe burden in terms of personal strain (35.96 ± 25.96) and role strain (30.13 ± 33.54). Gender (𝑋 2 = 6.630; p = 0.01), type of family (𝑋 2 = 8.420; p = 0.004) and employment status of caregivers (𝑋 2 = 4.069; p = 0.044) were significantly associated with the level of perceived burden. The study found no significant correlation between coping strategies and burden, however, the direction of correlation suggested an inverse correlation between problem-focused coping and burden (r = −0.141; p = 0.112). Effective coping strategies, especially problem-focused coping strategies, can help minimize caregiver burden. However, caregivers living in nuclear families are more likely to experience higher levels of burden. These findings highlights the need for targeted support and counseling services to assist caregivers and reduce their overall burden.